Organ system improvements in Japanese patients with systemic lupus erythematosus treated with belimumab: A subgroup analysis from a phase 3 randomized placebo-controlled trial. Issue 2 (3rd March 2020) - Tanaka, Yoshiya; Bass, Damon; Chu, Myron; Egginton, Sally; Ji, Beulah; Roth, David
Abstract: Objectives: To assess the effects of belimumab on disease activity across multiple organ domains in Japanese patients from the Phase 3 randomized, double-blind, North-East Asia study, BEL113750 (NCT01345253). Methods: Patients, aged ≥18 years, with American College of Rheumatology-defined systemic lupus erythematosus (SLE) and a Safety of Estrogen in Lupus Erythematosus National Assessment-SLE Disease Activity Index (SELENA-SLEDAI) score ≥8 at screening, on stable SLE treatment, were randomized 2:1 to receive intravenous belimumab 10 mg/kg or placebo, plus standard of care, on Days 0, 14, and 28, then 4-weekly until Week 48. Patients were assessed for SELENA-SLEDAI and British Isles Lupus Assessment Group (BILAG) organ system improvement/worsening between baseline and Week 52. Results: Sixty patients (belimumab, n = 39; placebo, n = 21) were enrolled in Japan. Improvement was seen in a greater proportion of belimumab patients, compared with placebo, in most SELENA-SLEDAI and BILAG domains (significant for the mucocutaneous domain). Worsening occurred in SELENA-SLEDAI hematologic and renal systems (<7% both treatments) and in a number of BILAG systems: <11% (placebo) and <8% (belimumab), although the small sample size should be noted. Conclusion: Organ system improvements were seen in more Japanese belimumab-treated than placebo-treated patients, providing further evidence supporting belimumab use in Japanese patients with SLE.